Preliminary Evaluation of a Social Skills Training and Facilitated Play Early Intervention Programme for Extremely Shy Young Children in China. Issue 6 (28th January 2016) - Li, Yan; Coplan, Robert J.; Wang, Yuemin; Yin, Jingtong; Zhu, Jingjing; Gao, Zhuqing; Li, Linhui
Abstract: The goal of this study was to provide a preliminary evaluation of a social skills and facilitated play early intervention programme to promote social interaction, prosocial behaviours and socio‐communicative skills among young extremely shy children in China. Participants were a sample of n = 16 extremely shy young children attending kindergarten in Shanghai, China. Children were randomly assigned to either the Social Skills Facilitated Play or comparison condition. Baseline, post‐intervention and 2‐month follow‐up measures included observations of children's social behaviours in quartets of novel peers. Result indicated that as compared with shy controls, shy children who participated in the Social Skills Training Facilitated Play programme were observed to demonstrate significantly greater post‐intervention frequencies of peer interactions (e.g. group play and peer conversation) and prosocial behaviours (e.g. cooperation, sharing and making/accepting social initiations) during unstructured free play with novel peers, as well as better social‐communicative competence during a speech task. Almost all of these improvements were maintained 2 months post‐intervention. Results are discussed in terms of the importance of developing and refining early intervention programmes for extremely shy young children in China. Copyright © 2016 John Wiley & Sons, Ltd.